(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
In this study, Cauchy dispersion relation for Germanium in a specific temperature were derived, and that dependent on temperature. The temperatures taken are ranging from 30 to 300 K and wavelengths from 1.8 to 5.5 m. The results of the computed refractive index were compared with a previously published data, and showed a good agreement.